Efficacy and Safety of Bicyclol Treatment for Non-Alcoholic Fatty Liver Disease: Results of a Cohort Study - I. Yu. Pirogova; S. V. Yakovleva; T. V. Neuymina; S. P. Sinitsyn; V. S. Chulkov; T. N. Shamaeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. This study is aimed at evaluating the efficacy and safety of Bicyclol administration in patients suffering from non-alcoholic fatty liver disease (NAFLD) («ZIGUN» research) by monitoring laboratory data and non-invasive methods of diagnosis of liver fibrosis and steatosis.Materials and methods.  The study included 93 patients with NAFLD with the average age of 44 (38–49) years, having the stage of liver fibrosis and steatosis greater than the 1st according to FibroScan (FibroScan 502 TOUCH with CAP software). Patients were randomized into 2 groups: 1) the main group comprised 67 patients receiving 75 mg/day of Bicyclol for 24 weeks in combination with aerobic exercise and Mediterranean diet; 2) the comparison group (26 patients) prescribed of only aerobic exercise and Mediterranean diet for 24 weeks.Results.  During Bicyclol treatment, a decrease in the following indicators was observed: ALT, AST, GGT, CRP by 30 % or more, glycated hemoglobin (–10 %) and HOMA-index (–24 %), cholesterol (–12 %), LDL (–19 %), triglycerides (–31 %), atherogenic coefficient (–22 %). A decrease to the1st stage of fibrosis was observed in 30 patients (44 %), steatosis regression to the 1st stage was noted in 57 patients (85 %). Liver steatosis of the 4th stage was not revealed after treatment with Bicyclol. The number of patients with indolent steatosis (less than 2nd stage) increased 2 times (p < 0.001). No significant changes were found in the group without drug therapy.Conclusions.  Bicyclol therapy in NAFLD is accompanied by positive dynamics of inflammation activity markers, insulin resistance and lipid spectrum, which suggests a positive dynamics of the stages of liver fibrosis and steatosis.